Arba'in nawawi recitation and its impact on juvenile delinquency prevention at mts ma’arif candimulyo - Azlan Shaiful Baharum; Fadhilatuz Zahro (Yayasan Azhar Amanaa Yogyakarta, 2025)
The Contribution of Arba'in Nawawi Recitation in Minimizing Juvenile Delinquency at MTs Ma'arif Candimulyo. Thesis, Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, Nahdlatul Ulama Islamic Institute Temanggung. Juvenile delinquency is an important problem that must be addressed immediately, until now there is a lot of news of juvenile delinquency such as cases of crime and bullying. The purpose of the research is to find out the contribution of Arba'in Nawawi's recitation in minimizing juvenile delinquency as well as the supporting and inhibiting factors of this activity. This study uses qualitative methods, phenomenological approaches, types of field research, primary and secondary data sources. The data collection technique uses observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and conclusion drawn, the researcher selects objects in MTs Ma'arif Candimulyo. The contribution in minimizing juvenile delinquency through the recitation of Arbain Nawawi is able to build morals and ethics, build character, self-control, increase intelligence and spiritual awareness. The supporting factors for the activity are the support from the school, support from parents who give permission to participate in the activity, students' awareness of the importance of the Arba'in Nawawi recitation, while the inhibiting factors are the lack of activity of students and there are still many students who are influenced by their friends not to take part in the recitation.